Correction: Know your enemy: Application of ATR-FTIR spectroscopy to invasive species control. - Claire Anne Holden; John Paul Bailey; Jane Elizabeth Taylor; Frank Martin; Paul Beckett; Martin McAinsh (PLoS ONE, 2022)
[This corrects the article DOI: 10.1371/journal.pone.0261742.].